2005
DOI: 10.1139/g04-123
|View full text |Cite
|
Sign up to set email alerts
|

Cerastodermaglaucum5S ribosomal DNA: characterization of the repeat unit, divergence with respect toCerastoderma edule, and PCR–RFLPs for the identification of both cockles

Abstract: The 5S rDNA repeat unit of the cockle Cerastoderma glaucum from the Mediterranean and Baltic coasts was PCR amplified and sequenced. The length of the units was 539-568 bp, of which 120 bp were assigned to the 5S rRNA gene and 419-448 bp to the spacer region, and the G/C content was 46%-49%, 54%, and 44%-47%, respectively. Two types of units (A and B), differing in the spacer, were distinguished based on the percentage of differences and clustering in phylogenetic trees. A PCR assay with specific primers for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…The presence of several 5S rDNA variants has been reported in other bivalve molluscs, such as Mytilus mussels (Insua et al 2001), the scallop Aequipecten opercularis (López-Piñón et al 2008), and the cockle Cerastoderma glaucum (Freire et al 2005), and in echinoderms (Caradonna et al 2007), arthropods (Keller et al 2006), and chordates (Martins and Galetti 2001;Daniels and Delany 2003). In other examples, 5S rDNA was found to be homogenized within the genome (Brown and Sugimoto 1974).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The presence of several 5S rDNA variants has been reported in other bivalve molluscs, such as Mytilus mussels (Insua et al 2001), the scallop Aequipecten opercularis (López-Piñón et al 2008), and the cockle Cerastoderma glaucum (Freire et al 2005), and in echinoderms (Caradonna et al 2007), arthropods (Keller et al 2006), and chordates (Martins and Galetti 2001;Daniels and Delany 2003). In other examples, 5S rDNA was found to be homogenized within the genome (Brown and Sugimoto 1974).…”
Section: Discussionmentioning
confidence: 87%
“…In several animal phyla, however, examples have been reported in which sequence divergence levels between ribosomal genes or spacers seem to be much higher than expected under a strict concerted evolution scenario (e.g., Insua et al 2001;Leo and Barker 2002;Freire et al 2005;Keller et al 2006;Sword et al 2007;Caradonna et al 2007;López-Piñón et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few criteria for morphological distinction between the two species, but none of them seemed to enable unequivocal separation at all sites of co-occurrence (Brock, 1978;Machado and Costa, 1994). Nevertheless, biochemical criteria and genetic markers are able to clearly distinguish both cockles (Brock, 1978;Brock, 1987;Brock and Christiansen, 1989;Hummel et al, 1994;André et al, 1999;Nikula and Väinölä, 2003;Freire et al, 2005;Ladhar-Chaabouni et al, 2010). Microsatellite primers designed for C. glaucum did not amplify DNA from C. edule, which also proves the separate character of these species (personal observation).…”
Section: Introductionmentioning
confidence: 99%
“…Some vertebrate species have the characteristic dual 5S rRNA gene system, as is the case for Xenopus, in which the two classes of 5S rRNA genes are regulated differently in somatic and oocyte cells (Komiya et al 1986). Two or more types of 5S rDNA have been identified in different species, characterized by remarkable differences in the NTS region, due mainly to single base changes as well as to insertions-deletions of repetitive motifs and/or relatively large sequences (Cloix et al 2000;Freire et al 2005;Morescalchi et al 2007). Furthermore, some authors have suggested that two classes of 5S tandem repeats could represent a general rule in fishes (Martins and Galetti 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…In this last group, intragenomic variation resulting from differences in the NTS region was reported only in the mussels Mytilus edulis and M. galloprovincialis (Insua et al 2001) and the cockle Cerastoderma glaucum (Freire et al 2005). In these two studies, the researchers assumed that the classes of 5S rDNA were organized in different chromosomal loci.…”
Section: Introductionmentioning
confidence: 99%